(untitled) (Journal of Economic Research & Business Administration, 2024)
This study examines the process and prospects of institutional integration of socially vulnerable segments of the population into the sphere of social entrepreneurship in Kazakhstan. The relevance of the topic is due to the need to develop effective mechanisms to solve social problems, increase employment and strengthen the social integration of these citizens. The purpose of the study is to identify obstacles and formulate recommendations for optimizing the institutional environment to stimulate social entrepreneurship and improve the well—being of vulnerable groups. The article presents an analysis of legal integration into the ecosystem of social entrepreneurship in Kazakhstan and theoretical aspects of institutionalization of this sector. The scientific significance of the work lies in the establishment of causal relationships between the institutionalization of social entrepreneurship and its potential for the integration of socially vulnerable groups. The analysis made it possible to identify key areas for improving the legislative and institutional environment, which contributes to a more effective integration of social entrepreneurship into the country’s economy and improving the well-being of vulnerable segments. The assessment of the current state and prospects for the development of social entrepreneurship was carried out on the basis of an analysis of scientific publications, statistical data and materials of public organizations. Economic and mathematical models helped to identify the most significant factors affecting the development of the sector. The contribution of the work is to prove the dynamism and variability of the institutional and legal process of integrating vulnerable groups of the population into the ecosystem of social entrepreneurship. The results of the study are of practical value and can be used to develop recommendations on creating a favorable environment for the development of social entrepreneurship and the integration of socially vulnerable groups into the economic structure of the country. Key words: social entrepreneurship, socially oriented entrepreneurship, institutional-legal integration, social entrepreneurship ecosystem.